RANCANG BANGUN SISTEM SMART HOME PADA RUMAH KOS BERBASIS INTERNET OF THINGS - Prananda Putra, Gede; Divayana, Yoga; Rahardjo, Pratolo (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i01.p16, 2022)
Technological developments in the field of electronics to date have made the human mindset advanced in the application of electronic equipment. One example of its development is remote control of electrical equipment. Many people use these developments as a means of facilitating life activities in solving problems that occur. The use of the internet in life can be used as an example in the use of technological developments. The internet is one of the communication media that has many benefits in increasing effectiveness, work efficiency, and monitoring. The internet can be used as a transmission medium for control and monitoring systems. With the internet, one can control electrical equipment and monitor the condition of the house. The concept originated from the Internet of Things or IoT. IoT is a concept where all tools and services in the system are connected to each other using internet media. Based on these problems, a smart home system was created that functions as control of electrical equipment, smoke detection, monitoring of temperature and humidity in the room. The monitoring and control system is integrated with Android applications and based on the Internet of Things.